Research on Mechanical Performance of CRTS III Plate-Type Ballastless Track Structure under Temperature Load Based on Probability Statistics - Zhiwu Yu; Ying Xie; Xiuquan Tian (Advances in Civil Engineering)
CRTS III (China Railway Track System III) slab ballastless track structure is one of the high-speed railway ballastless track structures which has Chinese independent intellectual property rights. The mechanical performance of CRTS III slab ballastless track structure under temperature load has not been clear yet. Therefore, through temperature field model and temperature load values selected by statistics analysis based on long-term meteorological data, the mechanical performance of ballastless track structure is studied under two typical working conditions with different safety probability. It is found that the daily extreme values of monthly axial uniform temperature and the daily maximum temperature gradient obey certain statistical laws. In addition, the maximum tensile stress of the self-compacting concrete layer is located in the middle and edge of the slab bottom and the side of the slab. The maximum tensile stress of the base plate is located at the edge of the surface of the layer and the inner edge of the limiting groove. The interface normal tensile stress is located at the end and corner of the interface. Furthermore, maximum stress increases with the increase of safety probability.